Bencana Alam Tak Terhindarkan: Sebuah Tinjauan Pariwisata Nias - Suparwoko - (Unisia, 2005)
Indonesian  tourism was grief due to the Bali bombing on October 12, 2002. The tsunami on December 2004 also made the Indonesian tourism was sorrow. The Aceh tsunami devastating some regions of Aceh and North Sumatra had killed more than 125.000 people. The sad feeling from the disaster was not overyet; however, the earthquake in Nias, North Sumatra, was happened just several months after the Aceh tsunami. Because of the Nias victims were more than 500 people, this Nias disaster was proposed as a national disaster. It was reasonable because the echo of the Nias earthquake was not only at regional level but also at the international level. Nias Island is well-known as an international surfing adventure, it was proved that aids from allover the world came to Nias. In this event, however, the condition of domestic and overseas tourists in Nias was not clear. The other question is how much the damage of the tourist facilities, particularly hotels, as the impact of the Nias disaster. This paper discusses the impact of the Nias earthquake focusing on some aspects of tourism, social-politic, regional economy, public and tourist facilities.